Combined liver–kidney transplantation versus liver transplant alone based on KDIGO stratification of estimated glomerular filtration rate: data from the United Kingdom Transplant registry – a retrospective cohort study. (28th March 2019) - Tinti, Francesca; Mitterhofer, Anna Paola; Umbro, Ilaria; Nightingale, Peter; Inston, Nicholas; Ghallab, Mohammed; Ferguson, James; Mirza, Darius F.; Ball, Simon; Lipkin, Graham; Muiesan, Paolo; Perera, M. Thamara P. R.
Summary: Patient selection for combined liver–kidney transplantation (CLKT) is a current issue on the background of organ shortage. This study aimed to compare outcomes and post‐transplant renal function for patients receiving CLKT and liver transplantation alone (LTA) based on native renal function using estimated glomerular filtration rate (eGFR) stratification. Using the UK National transplant database (NHSBT) 6035 patients receiving a LTA ( N = 5912; 98%) or CLKT ( N = 123; 2%) [2001–2013] were analysed, and stratified by KDIGO stages of eGFR at transplant (eGFR group‐strata). There was no difference in patient/graft survival between LTA and CLKT in eGFR group‐strata ( P > 0.05). Of 377 patients undergoing renal replacement therapy (RRT) at time of transplantation, 305 (81%) and 72 (19%) patients received LTA and CLKT respectively. A significantly greater proportion of CLKT patients had severe end‐stage renal disease (eGFR < 30 ml/min/1.73 m 2 ) at 1 year post‐transplant compared to LTA (9.5% vs. 5.7%, P = 0.001). Patient and graft survival benefit for patients on RRT at transplantation was favouring CLKT versus LTA ( P = 0.038 and P = 0.018, respectively) but the renal function of the long‐term survivors was not superior following CLKT. The data does not support CLKT approach based on eGFR alone, and the advantage of CLKT appear to benefit only those who are on established RRT at the time of transplant.